Peningkatan Pengetahuan Masyarakat Tentang Kesehatan Melalui Home Care Pada Masyarakat Blimbing Tarokan Kabupaten Kediri - Vitaria Wahyu Astuti; Maria Anita Yusiana; Selvia David Richard; Heru Suwardianto (Pelita Abdi Masyarakat, 2021)
Background: Health is the right of every human being as stated in the Law, so it is possible that every individual has the same rights in health services. The elderly are a group that is vulnerable to all diseases, physical weakness and living alone is one of the factors that causes the elderly to not be able to get good health services. The problems faced by the elderly in Blimbing Tarokan Village are the lack of knowledge of the elderly in managing the disease they are experiencing and the lack of awareness of the elderly to seek regular treatment. The purpose of this PkM activity is to carry out health checks and provide health education by making visits to the homes of elderly people who are targeted by Community Engagement. Method: The method of community service provided is to check blood pressure, pulse, breath and blood sugar checks and provide health education about diseases suffered by the elderly, the management of the diseases they suffer from, from understanding the disease to management both pharmacologically and non-pharmacologically. Results: Based on the results found by the servant, the elderly seemed enthusiastic and active in asking questions about disease management, especially about medication and what to eat and what not to eat. Conclusion: Health services to the community through home care can increase the knowledge of the elderly about their illnesses and the management that must be carried out routinely.